(untitled) (Archives of Mechanics - Test, 2008)
The steady flow of Herschel–Bulkley fluid through an inclined tube of non-uniform cross-section with multiple stenoses has been investigated. Assuming the stenoses to be mild, the flow equations have been linearised and the expressions for resistance to the flow and wall shear stress have been derived. The effects of various parameters on these flow variables have been studied. It is found that the flow resistance increases with the heights of the stenoses, yield stress, power law index, but decreases with inclination. Further, the shear stress increases with plug core region radius.